CHARACTERISTICS OF ACCOUNTING IN THE ECONOMIC ACTIVITY OF SMALL ENTERPRISES I, PROBLEMS AND IMPROVEMENT (World Economics and Finance Bulletin, 2022)
It is known that small business plays an important role in the country's economy. As long as small business is successfully operating in the economy , it contributes to the economic and social development of the country efficient affects and _ social tension reduces _ Small business entities for financial of resources farm , given its limited tasks assigned to the managing entity to perform damage keeping accounting records without reporting procedures maximum level simplification the most current is an issue . Small enterprise own activity and management needs, their complexity and employees from number based on the form of accounting himself he has the right to choose . That's it with together , small the basis of enterprise accounting principles in compliance with applicable accounting records own of work to himself special features adaptation can _ Accounting simplified shape set up an account on in reaching small standard Plan of Accounts to enterprises on the basis of accounts the plan make up recommendation will be done . The majority small enterprises for main from problems One of them is the organization of accounting reach necessity right is not understanding . In practice, there are also cases where b uxhalteria policy often inaccurate, without comprehensive analysis, that is, only the tax inspectorate for developed . This and finally, the following basic of accounting duties to perform leading to suspension comes : economic activity processes i and results about full and reliable information formation ; of property existence and movement, rational use of production resources over control provide ; internal identification of production resources ; financial and economic in the activity timely prevention of negative events get _ assess the actual use of identified resources . This article examines the characteristics of accounting in small enterprises, identifies the main problems , and suggests ways to improve accounting.
Keywords: accounting; accounting standards; small enterprise; accounting problems